Promoting Inclusion through Democratic Education: Strategies and Implications - Sapkota, Madhabi; Niure, Dhurba Prasad (ILAM इलम, 2024)
This article aims to explore various strategies that could be used to promote inclusion through a democratic education system. It was prepared based on a number of literature sources concerning inclusion and the democratic process. The reviewed literature was sourced from libraries and various search engines. The collected information was then systematically organized into eight themes reflecting strategies required to promote inclusion through the democratic process. Different approaches, such as ensuring equal access to education for all children including those with special needs, creating a welcoming environment for all, providing multiple ways of learning to accommodate diverse learning styles of learners, promoting inclusion in the classroom, and optimizing participation of learners in decision-making processes, can be practiced to enhance the inclusion through the democratic education process. Furthermore, respecting individual rights, fostering collaborative learning environments, and promoting transparency and accountability in educational practices could also be useful in maximizing inclusion through the democratic process.